Analisis of Spelling Errors in Student Thesis Malikussaleh University Business Administration Process Print Year 2022 - Linasari, Mei; Khalsiah; Wulanda (Journal of Practice Learning and Educational Development, 2026)
This research is based on observations made by the researchers on the theses of students in the Business Administration Study Program and the discovery of many spelling errors in the thesis writing. This study aims to identify and analyze spelling errors found in the theses of students from the Business Administration Study Program, Faculty of Social and Political Sciences, Malikussaleh University, published in 2022. The approach used in this research is qualitative descriptive with data collection methods through systematic reading and note-taking techniques. The main focus of the study is on errors in the use of capital letters, italics, abbreviations, prepositions, and periods in thesis writing. The analysis results show that there are various forms of significant spelling errors that have the potential to affect the quality and clarity of academic writing. These findings indicate the need to improve students' understanding and skills in applying correct spelling rules in accordance with the Enhanced Indonesian Spelling System (EYD) Edition V. It is hoped that this research can serve as evaluation material for the academic community in efforts to improve the quality of scientific writing at the Faculty of Social and Political Sciences, Malikussaleh University. Furthermore, the results of this study can also be used as a basis for developing more effective language and academic writing development programs in the future.